Unraveling the Microstructure‐Related Device Stability for Polymer Solar Cells Based on Nonfullerene Small‐Molecular Acceptors. Issue 16 (28th February 2020) - Du, Xiaoyan; Heumueller, Thomas; Gruber, Wolfgang; Almora, Osbel; Classen, Andrej; Qu, Jianfei; He, Feng; Unruh, Tobias; Li, Ning; Brabec, Christoph J.
Abstract: As the power conversion efficiency (PCE) of organic solar cells (OSCs) has surpassed the 17% baseline, the long‐term stability of highly efficient OSCs is essential for the practical application of this photovoltaic technology. Here, the photostability and possible degradation mechanisms of three state‐of‐the‐art polymer donors with a commonly used nonfullerene acceptor (NFA), IT‐4F, are investigated. The active‐layer materials show excellent intrinsic photostability. The initial morphology, in particular the mixed region, causes degradation predominantly in the fill factor (FF) under illumination. Electron traps are formed due to the reorganization of polymers and diffusion‐limited aggregation of NFAs to assemble small isolated acceptor domains under illumination. These electron traps lead to losses mainly in FF, which is in contradistinction to the degradation mechanisms observed for fullerene‐based OSCs. Control of the composition of NFAs close to the thermodynamic equilibrium limit while keeping adequate electron percolation and improving the initial polymer and NFA ordering are of the essence to stabilize the FF in NFA‐based solar cells, which may be the key tactics to develop next‐generation OSCs with high efficiency as well as excellent stability. Abstract : Fill factor losses in nonfullerene‐acceptor‐based organic solar cells under illumination are caused by morphological traps due to diffusion limited aggregation of the nonfullerene acceptors in the mixed matrix. To achieve stable and high‐performance organic solar cells under illumination, it is essential to engineer the mixed regions from both thin‐film formation kinetics and materials intrinsic properties, e.g., materials compatibility and diffusion constant.